Central Sensitization of Mechanical Nociceptive Pathways Is Associated with a Long-Lasting Increase of Pinprick-Evoked Brain Potentials - van den Broeke, Emanuel N.; Lambert, Julien; Huang, Gan; Mouraux, André (Frontiers in Human Neuroscience, 2016)
Intense or sustained nociceptor activation, occurring, for example, after skin injury, can induce “central sensitization”, i.e. an increased responsiveness of nociceptive neurons in the central nervous system. A hallmark of central sensitization is increased mechanical pinprick sensitivity in the area surrounding the injured skin. The aim of the present study was to identify changes in brain activity related to this increased pinprick sensitivity. In 20 healthy volunteers, increased pinprick sensitivity was induced using high frequency electrical stimulation of the forearm skin (HFS). Mechanical pinprick stimulation (64 and 90 mN) was used to elicit event-related brain potentials (ERPs). The recordings were performed before, 20 minutes after and 45 minutes after applying HFS. The contralateral non-sensitized arm served as control. Pinprick stimulation of 64 mN, but not 90 mN, applied in the area of increased pinprick sensitivity elicited a significant increase of a late-latency positive wave, between 300 and 1100 ms after stimulus onset and was maximal at midline posterior electrodes. Most importantly, this increase in EEG activity followed the time course of the increase in pinprick perception, both being present 20 and 45 minutes after applying HFS. Our results show that the central sensitization of mechanical nociceptive pathways, manifested behaviorally as increased pinprick sensitivity, is associated with a long-lasting increase in pinprick-evoked brain potentials provided that a 64 mN stimulation intensity is used.